Genetic mechanisms and a stability evaluation of large landslides in Zhangjiawan, Qinghai Province - Wu, Yuanzao; Dong, Yangdan; Wei, Zhanxi; Dong, Jianhui; Peng, Liang; Yan, Pan; Ma, Wenli (Frontiers in Earth Science, 2023)
It is very important to study the instability law of typical landslides for the understanding of regional landslides evolution and disaster prevention. This paper takes the Zhangjiawan landslide in Xining City, Qinghai Province as an example. Through field survey and analysis of the geological environment conditions, the formation and evolution mechanisms of Zhangjiawan landslide are summarized. The stability of the Zhangjiawan landslide is evaluated by limit equilibrium method and numerical simulation method to provide a theoretical support for the susceptibility of the Zhangjiawan landslide. The results show that the main reasons for the occurrence of multi-grade landslides are the steep and gentle terrain changes, the poor permeability of mudstone lithology, the excavation of front anti-slide section and rainfall. The whole deformation and failure mechanism of the landslide is "unloading rebound-tension deformation-creep deformation". The results of the numerical simulation method and the limit equilibrium method are almost the same, and the difference in stability coefficients is small. In the rainstorm condition, the displacement and the maximum shear strain increments are mainly concentrated on the rear edge of the landslide mass and the front edge is obviously pushed, which is a typical push-type landslide.